Sistema de gestión contable financiera para el centro de salud tipo "A" medicenter de la ciudad de Mira, provincia del Carchi - Imbaquingo Benalcázar, Edwin Rolando (2018)
The accounting and financial management is the fundamental basis of the business information system, ¡ts proper management makes it one of the useful tools for planning, organization, management, control and evaluation of business management. For the present work, the objective of the design ofa Financial Accounting Management System forthe Type "A" Health Center - Medicenter was proposed, this design was characterized by a planned process according to the business context, becoming a valid document for The decision- making methodology was based on the mixed qualitative-quantitative modality, type of bibliographic applied research through the collection of theoretical and field information with the collection of information in the site where the activities are developed, techniques such as the survey, interview and tools such as interview guide and questionnaire, making it possible to obtain a diagnosis of the current situation, The proposal developed administrative tools such as mission, vision, objectives, corporate values, flowcharts of administrative and accounting processes, asset inventories fixed, accounting record from documents were You will even present financial statements, this in order to provide information on the current economic situation of the health center and offer the administration a quality work that allows an efficient control of health services.